2014
DOI: 10.1051/e3sconf/20140301016
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Carbon Emission Reduction for Buildings Projects in Malaysia-A Comparative Analysis

Abstract: Abstract. The Malaysian construction industry significantly contributes as an empowerment to its development vision of 2020 by reducing 40% of carbon emission. Moreover, this industry accounts as a threat to the environment, not only in terms of consumption of natural resources but also in emitting million tons of carbon emission annually. In fact, Malaysia is categorized the 30th in the world's ranking in carbon emission level. To mitigate the raise of carbon emission level from the buildings construction, se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 7 publications
0
16
0
Order By: Relevance
“…The challenge in sustainably advancing the building sector is the increasingly large outflows of CO 2 due to the utilization of non-sustainable energy sources in the planning, construction, and operations of buildings [9]. CO 2 is also emitted from the broad utilization of land in the urbanization process [11]. The energy sourced from fossil fuels is non-sustainable, and yet it accounts for a large percentage of the energy used in the construction and operation processes.…”
Section: Issues and Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…The challenge in sustainably advancing the building sector is the increasingly large outflows of CO 2 due to the utilization of non-sustainable energy sources in the planning, construction, and operations of buildings [9]. CO 2 is also emitted from the broad utilization of land in the urbanization process [11]. The energy sourced from fossil fuels is non-sustainable, and yet it accounts for a large percentage of the energy used in the construction and operation processes.…”
Section: Issues and Challengesmentioning
confidence: 99%
“…Building contributes approximately 39% of the annual global CO 2 [10] (Figure 1). It has been reported that more than a third of the usage of total energy and CO 2 emissions is a result of the building sector in the developed and developing nations [11]. Therefore, CO 2 emission mitigation measures are crucial [12].…”
Section: Introductionmentioning
confidence: 99%
“…Malaysia is one of the major manufacturing hubs in ASEAN countries, and remarkable development in this sector is accompanied by high atmospheric CO 2 concentrations [26]. Generally, there are four sources of GHGs emission in manufacturing and construction sectors: (i) Manufacture and transportation of building materials, (ii) Energy consumption of construction equipment, (iii) Energy consumption of processing resources and (iv) Disposal of construction wastes [27]. Figure 1 shows the different sectors for CO 2 emission in Malaysia [22].…”
Section: Malaysia's Position In Co 2 Emissions and Ccsmentioning
confidence: 99%
“…In terms of sectorial percentage, 24% of total carbon dioxide comes from the construction sector in the country [12]. In Malaysia, residential building in construction sector consists of 29.9% of total value of construction work done in the first quarter of 2015 [13].…”
Section: Literature Reviewmentioning
confidence: 99%